Recuerdo de una esperanza : la Segunda República en Alicante (1931-1936) : [exposición] / [coordinación, Francisco Moreno Sáenz ; textos, Juan Martínez Leal, Francisco Moreno Sáez, Mónica Moreno Seco] - Martínez Leal, JuanMoreno Sáez, Francisco (1942-) Moreno Seco, Mónica
Título tomado de la cubierta